Identification of Causative agents associated with decay of Trees Twig and Orchards Die-back and their Impacts on Vessels of Citrus, Date Palm and Ficus: Causal Organisms of Trees Twig and Orchards Die-back - Alshammari, Nawaf; Bairum, Randa S.; Sulieman, Abdel Moneim E.; Jamal, Arshad; Elamin, Hassan B.; Elamin, Salwa M.; Upadhyay, Tarun Kumar; Doleib, Nada M.; Albulaihed, Yazeed; Saeed, Mohd (Cellular and Molecular Biology, 2022)
The present work is concerned with the studies of the organism causing wood decay of twigs and branches of citrus orchards, date palm Phoenix dactylifera L, and ficus trees. A survey for the occurrence of this disease in the main growing areas was achieved by the researchers. The following species of citrus orchards [lime (C. aurantifolia), sweet orange (C. sinensis), and mandarin (C. reticulate)] were surveyed, and so date palm and ficus trees. However, the results showed that the incidence of this disease was about 100%. Laboratory examinations data revealed mainly two fungal species causing the disease: Physalospora rhodina (P.rhodina) and Diaporthe citri (D. citri). In addition that, both fungi, which are P. rhodina and D. citri affected the vessels of tree tissues. According to the pathogenicity test, the fungus P. rhodina caused a breakdown of parenchyma cells, and the fungus D. citri caused the darkening of the xylem.